2002
DOI: 10.1046/j.1365-2796.2002.00998.x
|View full text |Cite
|
Sign up to set email alerts
|

Validity of D‐dimer tests in the diagnosis of deep vein thrombosis: a prospective comparative study of three quantitative assays

Abstract: ) showed sensitivities of 90 and 88%, specificities of 42 and 44%, and NPV's of 85 and 83%, respectively. The Nycocard Ò D-dimer assay showed a sensitivity of 63%, specificity of 67% and NPV of 71%. Conclusions. The diagnostic performance of VIDAS New Ò and the Auto Dimer Ò D-dimer assays is almost identical, but this study suggests that neither of the D-dimer assays is suitable as the only screening method for DVT, in a situation with a high pretest probability of DVT. This call for a differential strategy th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
2
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 20 publications
1
14
2
2
Order By: Relevance
“…The authors state that the sensitivity of the assay was 98% (95% confidence interval, 90%-100%) and the negative predictive value (NPV) was 99% (95% confidence interval, 95%-100%). This is in contrast to a recent article by Larsen and colleagues, 2 who assessed the reliability of the same D-dimer assay (Table). Using the discriminant values suggested by the manufacturer, the VIDAS kit has a sensitivity of 90%, a specificity of 42%, and an NPV of 85%.…”
contrasting
confidence: 62%
“…The authors state that the sensitivity of the assay was 98% (95% confidence interval, 90%-100%) and the negative predictive value (NPV) was 99% (95% confidence interval, 95%-100%). This is in contrast to a recent article by Larsen and colleagues, 2 who assessed the reliability of the same D-dimer assay (Table). Using the discriminant values suggested by the manufacturer, the VIDAS kit has a sensitivity of 90%, a specificity of 42%, and an NPV of 85%.…”
contrasting
confidence: 62%
“…For other assays, lower specificities were obtained in our study population: Auto Dimer reported sensitivities between 90 and 99% and specificities from 39 to 57% [30,33], and Innovance reported a sensitivity of 99% and a specificity of 39.1% [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent investigation was less convincing. In one study sensitivity in DVT diagnosis was described to be as low as 63% (38). Our results were also disappointing and prevent us from recommending this assay for routine use.…”
Section: D-dimer Poc Assaysmentioning
confidence: 69%